Fugitive emission estimation from storage tank and wastewater treatment units - Har, Jonathan Sean Hou (2013)
The objective of this study is to develop a systematic method for estimating fugitive emission from storage tank and wastewater treatment (WWT) units. Fugitive emission is the unintentional release of chemical vapors or gases that occur whenever there are discontinuities in the solid barrier maintaining the containment. While the amount released is very small, continuous exposure to chemical substances due to emission may adversely affect workers’ health. To achieve the objectives, a comprehensive review is conducted on currently available fugitive emission estimation methods. A combination of emission factor, equation and software techniques is chosen as the methodology to study fugitive emission from storage tank and WWT units. A total of eleven horizontal and vertical tanks as well as nine WWT units are selected in this study. The results are presented as precalculated fugitive emission database for storage tank and WWT units. Dimensions data for storage tank and WWT units are also compiled from various sources for estimating chemical concentration. Three examples are given to demonstrate the application of the precalculated fugitive emission database in estimating fugitive emission and concentration from storage tank and WWT units. To calculate the other losses (e.g. working loss and evaporation loss), TANKS 4.09d software and evaporation loss equation are used. The typical range of fugitive emission individual stream value for both storage tank and WWT units are found to be within 0.01-0.20 kg/h. Calculation using the EPA emission factor leads to higher emission estimates compared to using the controlled emission value. Evaporation loss is found to be the largest source of emission loss from storage tank and WWT compared to fugitive emission, working and breathing losses